Kajian Upaya Peningkatan Pelayanan Angkutan Antarmoda Di Jakarta - Suliyanti, Rini (Warta Penelitian Perhubungan, 2010)
Higlrwai1 transportation StJStenz disruption due to the lzigh lerel of complexihJ is the potential complexihJof the problem of transportntion in Greater ]nknrtn mncro is ven1 large.To increase inter-mode transport senrice ns nn impl.emelltntion of the mncro problem of transportationin Greater Jnknrta have made n pattern of policies tluzt support, including transportation demandmanagement, appropriate land use planning, economic instruments, integration of transport modeswith no motor, mvareness and public support, sustainabilihJ funding ..Transportation StJStem a few countries am provide some possible solutions to tackle the problem oftransportation in Greater Jaknrta mncro abaue is to reduce primte 11ehicle, expand road capacihj,imprauing infmstn1cture facilities 111lzic11 must be inrfepe11rfent PT.KAI 7lrith n snuzll subsidy, increasingthe number of public transport, nlllt Suc/1 entrepreneurs prmride softloon to this public vehiclessuch as Metromini, PPD, Mmjasnri de11otion, Ferris, Kopnja so that it can renew its fleet and able tomanage as a feeder of the buswai; StJStem.Keywords: Pattern Policies tlmt support inter-mode transport sennce improvement, Qualitative Annlysis